2019
DOI: 10.1194/jlr.m086413
|View full text |Cite
|
Sign up to set email alerts
|

The role of X-box binding protein 1 in the hepatic response to refeeding in mice

Abstract: Abbreviations: Acc, acyl-CoA carboxylase; CHOP, C/EBP homologous protein; Dgat2, diacylglycerol acyl-transferase 2; Dr5, death receptor 5; Edem, endoplasmic reticulum degradation enhancing mannoside; eIF2, eukaryotic initiation factor 2; ERo1, endoplasmic reticulum oxidase 1; IRE1, inositol requiring enzyme 1; Scd-1, stearoyl-CoA desaturase 1; Trb3, Tribbles-related protein 3; UPR, unfolded protein response; XBP1, X-box binding protein 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The same publication showed that Xbp1s LKO mice had decreased plasma levels of TGs, due to an impaired secretion by the liver, in both fasting and refeeding states. This strengthened the idea that the function of XBP1s in hepatic lipid metabolism is not restricted to lipogenesis 74 . A similar observation was made during the characterization of a conditional postnatal Xbp1 KO in mice liver, in which decreased levels of plasma TGs, cholesterol and free FAs were observed in KO animals compared to controls 70 .…”
Section: Regulation Of Lipid Metabolism By the Uprsupporting
confidence: 77%
See 2 more Smart Citations
“…The same publication showed that Xbp1s LKO mice had decreased plasma levels of TGs, due to an impaired secretion by the liver, in both fasting and refeeding states. This strengthened the idea that the function of XBP1s in hepatic lipid metabolism is not restricted to lipogenesis 74 . A similar observation was made during the characterization of a conditional postnatal Xbp1 KO in mice liver, in which decreased levels of plasma TGs, cholesterol and free FAs were observed in KO animals compared to controls 70 .…”
Section: Regulation Of Lipid Metabolism By the Uprsupporting
confidence: 77%
“…This strengthened the idea that the function of XBP1s in hepatic lipid metabolism is not restricted to lipogenesis. 74 A similar observation was made during the characterization of a conditional postnatal Xbp1 KO in mice liver, in which decreased levels of plasma TGs, cholesterol and free FAs were observed in KO animals compared to controls. 70 A possible explanation for these results came from a later study which showed that XBP1 overexpression was able to revert deficient secretion of TGs in hepatocytes from liver-specific Ern1a KO mice by increasing protein disulphide isomerase (PDI) expression.…”
Section: Regulation Of Lipid Metabolism By Ire1αsupporting
confidence: 66%
See 1 more Smart Citation
“…65 Mice lacking hepatic XBP1 had markedly decreased mRNA levels of SREBP1, FAS, and ACC1. 66,67 It has been reported that the RNAi-mediated knockdown of ATF6 in hepatocytes could block fatty acid-induced SREBP-1c expression. 68 In this study, the expression of proteins related to ERS and lipogenesis were measured, and our findings agreed with those of previous studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The contribution of the other two arms of the UPR to the regulation of lipid metabolism is also evident. Inositol-requiring enzyme 1a (IRE1a) regulates lipid metabolism via X-box binding protein 1 (XBP1) and regulated IRE1dependent decay (RIDD), to control the transport of triglycerides and proliferator-activated receptor a (PPARa)-mediated lipolysis, and to promote lipid hydrolysis and prevent lipid storage, respectively [50][51][52]. Examples of the regulation of lipid metabolism through eukaryotic Initiation Factor 2 (eIF2a), ATF4 and C/EBP homologous protein (CHOP), which constitute downstream targets of protein kinase RNA-like ER Kinase (PERK) signaling, include lipogenesis, and FA elongation and FA desaturation [53,54].…”
Section: Triangular Interplay Between Cellular Stress Lipid Metabolis...mentioning
confidence: 99%